Solve for n 7=-2n+1

Math
7=-2n+1
Rewrite the equation as -2n+1=7.
-2n+1=7
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Subtract 1 from both sides of the equation.
-2n=7-1
Subtract 1 from 7.
-2n=6
-2n=6
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2n=6 by -2.
-2n-2=6-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2n-2=6-2
Divide n by 1.
n=6-2
n=6-2
Divide 6 by -2.
n=-3
n=-3
Solve for n 7=-2n+1

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top